PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. MUSTIKA RATU TBK CIRACAS, JAKARTA TIMUR - Hotman Napitupulu (Jurnal Ekonomi dan Industri, 2020)
This study aims to determine and analyze the effect of compensation, work environment on employee performance at PT. Mustika Ratu Tbk Ciracas, East Jakarta. The data collection technique used was to spread questionnaires. The data analysis technique used is descriptive analysis and multiple linear regression analysis. The results of the study using multiple linear regression analysis showed that compensation and work environment had a positive and significant effect on the employee performance of PT. Mustika Ratu. Compensation has a positive and significant effect on the performance of employee PT. Mustika Ratu, while the work environment has a positive and significant effect on the employee performance of PT. Mustik Ratu. Thus the hypothesis in this study is that it is assumed that compensation and work environment have a positive and significant effect on the employee performance of PT. Mustika Ratu.